Phylogeny and prevalence of filarial parasites (nematoda: onchocercidae) from the common treeshrew (Tupaia glis) in Peninsular Malaysia / Ahmad Syihan Mat Udin - Ahmad Syihan , Mat Udin (2022)
Filarial nematodes cause lymphatic filariosis and zoonotic diseases in humans. However, the origins and evolution of these group of parasites is still unclear because the ancestral species has not yet been discovered. This study reviews the taxonomic and phylogenetic relationship of filarial parasites from common treeshrews, Tupaia glis. The study also intends to determine the prevalence of filarial parasites in relation to the distribution of hosts in Peninsular Malaysia. Cage trapping techniques were used to capture host animals in selected sites throughout Peninsular Malaysia. A total of 98 common treeshrews were captured and examined. Two adult species of filarial parasites, Malayfilaria sofiani and Mansonella dunni were identified, and data on their distribution and prevalence was recorded. The parasites were subjected to details morphological and molecular analyses. Polymerase chain reaction (PCR) was performed using cox1 and 12S rRNA genes. Phylogenetic analysis indicated that M. dunni have a close affinity with Mansonella ozzardi which is a human parasite in South America, but their genetic distance was substantially large (p-distance 6.1-6.4%). M. sofiani appears to be closely related to Wuchereria spp. and Brugia spp. but differs based on several morphological characteristics. The Kimura 2-parameter distance between the cox1 gene sequences of M. sofiani and W. bancrofti was 11.8%. Molecular analyses indicated that M. sofiani differs from both W. bancrofti and Brugia spp. at the genus level. The total percentage of prevalence was 31% with 30 individuals of common treeshrews were infected. M. sofiani adult is only restricted to secondary forest of Jeram Pasu, Kelantan with 6.1% prevalence whereas M. dunni have a 23.4% prevalence and widely distributed in primary and secondary forest of Peninsular Malaysia. No adult Brugia tupaiae was found in this study, however one common treeshews from Gemas, Negeri Sembilan was infected with microfilaria of Brugia tupaiae. This study concluded that Malayfilaria sofiani appears to be a new genus and new species. while Mansonella dunni was closely related to human parasite, M. ozzardi and M. perstans. Only one common treeshews from Gemas, Negeri Sembilan was infected with B. tupaiae. Contrary to previous studies, there is a significant decrease in prevalence of B. tupaiae. Fortunately, there was no filariasis cases associated with filarial parasites of common treeshrews was reported recently. Filarial parasites are one of the agents of emerging zoonotic diseases. This study serves as a guide for medical practitioners and other authority to pinpoint the distribution of treeshrews filarial parasites. The present study provides molecular and morphological data that can be used to identify the filarial parasites, if zoonotic cases involving human occurs.